Primary Mitral Valve Regurgitation Outcome in Patients With Severe Aortic Stenosis 1 Year After Transcatheter Aortic Valve Implantation: Echocardiographic Evaluation - Florentino,Thiago Marinho (2017)
Abstract Background: Mitral valve regurgitation (MR), present in up to 74% of the patients with severe aortic stenosis (AS), can be a negative prognostic factor when moderate or severe. The outcome of MR after percutaneous transcatheter aortic valve implantation (TAVI) and predictors associated with that outcome have not been well established in the literature. Objective: To assess the outcome of primary MR in patients submitted to TAVI and to identify associated factors. Methods: Observational study of patients with symptomatic severe AS submitted to TAVI from January 2009 to April 2015 at two specialized centers. Echocardiographic outcome was assessed with data collected before and 1 year after TAVI. Results: Of the 91 patients with MR submitted to TAVI and followed up for at least 12 months, 67 (73.6%) had minimum/mild MR before the procedure and 24 (26.4%) had moderate/severe MR. Of those with minimum/mild MR, 62 (92.5%) had no change in the MR grade (p < 0.001), while 5 (7.5%) showed worsening. Of those with moderate/severe MR, 8 (33.3%) maintained the same grade and 16 (66.7%) improved it (p = 0.076). Patients with moderate/severe MR who improved MR grade had lower EuroSCORE II (p = 0.023) and STS morbidity (p = 0.027) scores, as compared to those who maintained the MR grade. Conclusion: MR grades change after TAVI. This study suggests a trend towards improvement in moderate/severe MR after TAVI, which was associated with lower preoperative risk scores.